Answer:
6 : 23
Step-by-step explanation:
![a : b = 3 : 4 ....(given)\\ \\ let \: a = 3x \\ b = 4x \\ \\ (6a - 3b) : (5a + 2b) \\ \\ = \frac{(6a - 3b)}{(5a + 2b)} \\ \\ = \frac{6(3x) - 3(4x)}{5(3x) + 2(4x)} \\ \\ = \frac{18x- 12x}{15x+ 8x} \\ \\ = \frac{6x}{23x} \\ \\ = \frac{6}{23} \\ \\ (6a - 3b) : (5a + 2b) = 6 : 23](https://tex.z-dn.net/?f=a%20%3A%20b%20%3D%203%20%3A%204%20....%28given%29%5C%5C%20%20%5C%5C%20let%20%5C%3A%20a%20%3D%203x%20%5C%5C%20b%20%3D%204x%20%5C%5C%20%20%5C%5C%20%286a%20-%203b%29%20%3A%20%285a%20%2B%202b%29%20%5C%5C%20%20%5C%5C%20%20%3D%20%20%5Cfrac%7B%286a%20-%203b%29%7D%7B%285a%20%2B%202b%29%7D%20%20%5C%5C%20%20%5C%5C%20%20%3D%20%5Cfrac%7B6%283x%29%20-%203%284x%29%7D%7B5%283x%29%20%2B%202%284x%29%7D%20%5C%5C%20%20%5C%5C%20%20%3D%20%20%5Cfrac%7B18x-%2012x%7D%7B15x%2B%208x%7D%20%5C%5C%20%20%5C%5C%20%20%3D%20%5Cfrac%7B6x%7D%7B23x%7D%20%5C%5C%20%20%5C%5C%20%20%3D%20%20%5Cfrac%7B6%7D%7B23%7D%20%20%5C%5C%20%20%5C%5C%20%286a%20-%203b%29%20%3A%20%285a%20%2B%202b%29%20%3D%206%20%20%3A%2023)
X = 16y^2 + 1
x - 1 = 16y^2
(x - 1)/16 = y^ 2
( (x-1) / 16 ) ^1/2 = y
( (x-1) ^ 1/2 ) / 4 = y
Answer:
x = 4, hope this helps!
Step-by-step explanation:
2x + 3 = 4x - 5
-2x -2x
3 = 2x -5
+5 +5
8 = 2x
divide by 2 on both sides
4 = x
switch where the x and 4 is, because teachers seem to like that
x = 4
Hi!
-6+7x-6x = 3
-6+x = 3
x = 3+6
x = 9
Answer:
x = 9
Answer:
C. 1.15<em>x</em> because adding 15% to the cost of the haircut is the same as multiplying the cost by 1.15.
Step-by-step explanation:
This answer is correct because, adding 0.15x (or 15%) to the total amount is the same as multiplying the cost by 1.15. This is because, the 1 that is added to 0.15 represents the total, since we are just multiplying instead of adding to it.
Hope this helps! :D